Perendaman Sari Belimbing Wuluh dengan Konsentrasi Berbeda terhadap Nilai pH dan Kadar Air Daging Paha Itik Magelang - Athi’ Nur ‘Azizah; Nur Hidayah; Pradipta Bayuaji Pramono (Wahana Peternakan, 2022)
Magelang duck is a native duck from Magelang Regency in Central Java. Duck meat has a higher fat content than chicken meat, making it more perishable. Meat quality can be maintained in various ways, one of them is using bilimbi fruit (Averrhoa bilimbi L.). The purpose of this study was to find out whether there was a differences in bilimbi fruit concentration in maintaning quality meat can lower pH value and water content of Magelang duck thigh meat. The ducks used in this study were two months old. This study used a Completely Randomized Experimental Design (CRD) with 4 treatments and 5 replications, then proceed with Duncan's Multiple Range Test (DMRT) if the treatments were different. The result showed that soaking bilimbi fruit for 30 minutes at a concentration difference of 20-60% significantly reduced the pH value of the Magelang duck thigh meat to 4,55-4,91, compared to 5,75 for controls. The water content did not affected by 57,01-59,85 value. The concentration of bilimbi fruit up to 60% was able to reduce the pH value of the Magelang duck thigh meat, but did not have an effect on the water content of the Magelang duck thigh meat. Keywords: bilimbi fruit, magelang duck, water content, pH value.